Measure the Impact of global financial crisis on some indicators of the Saudi Arabia’s economy using the Mendel-Fleming model for period (1997-2015) - الباشا الصديق محمد; البشير تماضر جابر (Journal of Economics and Administrative Sciences, 2018)
The main objective of this study is to measure the Impact of global financial crisis on some indicators of the Saudi Arabia’s economy using the Mendel-Fleming model, the importance of the study applied by focusing on the theme of general equilibrium in the face of fluctuations in the global economy. Study used a descriptive approach and the methodology of econometrics to construct the model. Study used Eviews Program for data analysis. The Data was collected from the Saudi Arabian Monetary Agency, for the period (1997-2014).Stationery of the variables was checked by Augmented Dickey-Fuller (ADF) and Phillips Perron (PP) unit roots tests. And also the co-integration’s test was done for the variables and found that the variables were integrated in the long run. Using OLS Method to estimate the model. The findings are as follows: influenced by macroeconomic indicators in Saudi Arabia’s global financial crisis. High Marginal Propensity to consume. Low in the exchange rate effect on the Import and Balance of Payments. Dummy variable showed the negative impact of the financial crisis on the balance of payments, The Interest rate a Macroeconomic indicator is influential on the decision to invest in Saudi Arabia.